Penyuluhan Dan Pelaksanaan Go Green Di Desa Citaleus, Kecamatan Buahdua, Kabupaten Sumedang - Raizal Fahmi; Sri Wilujeng; Reni Srimulyaningsih; Ina Darliana; Ishak Tan (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The solution that can be applied to the community to deal with the impact of global warming today is the concept of "go green". However, the problem is that the application of this "go green" solution has not been widely applied in the community, especially in communities that are directly adjacent to and dependent on forests. Therefore, the the academic community of the Faculty of Forestry, Winaya Mukti University conducted forestry counseling on go green in community service activities to provide awareness to people living in villages bordering forests in Sumedang Regency, precisely in Citaleus Village. This research was carried out using the method of counseling and practicing planting forestry plant seeds. The results of this research succeeded in achieving a satisfactory level to provide and introduce knowledge about going green and the practice of implementing it by planting forestry plant seeds for the people of Citaleus Village, Buahdua District, Sumedang Regency. This success is evidenced by the positive response from the analysis results received by the service team.